Acute White Matter Differences in the Fornix Following Mild Traumatic Brain Injury Using Diffusion Tensor Imaging. Issue 2 (17th November 2010) - Yallampalli, Ragini; Wilde, Elisabeth A.; Bigler, Erin D.; McCauley, Stephen R.; Hanten, Gerri; Troyanskaya, Maya; Hunter, Jill V.; Chu, Zili; Li, Xiaoqi; Levin, Harvey S.
ABSTRACT The integrity of the fornix using diffusion tensor imaging (DTI) in adolescent participants with acute mild traumatic brain injury (mTBI) compared to a demographically matched control group was examined. Fractional anisotropy (FA) in the fornix was elevated in the mild traumatic brain injured group. Performance on the Automated Neuropsychological Assessment Metrics (ANAM) was lower in the group with mTBI. A relation was found between lower performance on cognitive tasks and higher FA. The potential role of fornix injury as a basis of memory and processing speed deficits in mTBI is discussed.